2012
DOI: 10.6018/eglobal.11.3.133721
|View full text |Cite
|
Sign up to set email alerts
|

Prejuicios de las enfermeras hacia la población inmigrante: Una mirada desde el Sur de España.

Abstract: RESUMENEn las últimas décadas España se ha convertido en un país receptor de inmigrantes, este aumento conlleva una creciente diversidad cultural en la sociedad que se refleja en el cambio del perfil cultural de los usuarios del sistema sanitario público.En este trabajo se ha marcado como objetivo tener una primera aproximación a los prejuicios que tiene el personal de Enfermería acerca de la población inmigrante.Metodología. Estudio cuantitativo transversal. Participantes: Personal de Enfermería de hospitales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 1 publication
2
5
1
1
Order By: Relevance
“…At the same time, nurses themselves think they should continue making an effort for immigrants to have a better quality of life. But these ideas are in contrast with the perception that immigrants receive more social assistance than Spaniards and that too many resources are devoted to the care of this social group, with immigrant patients being considered responsible for the collapse of our health system, which could in a not too distant future lead to serious health and social problems, coinciding with ideas obtained by different studies (1,17,(22)(23)(24)(25)(26) . Although this is the perception of nurses, it has been demonstrated that immigrants do not use hospital services more frequently than the native population nor is this use more burdensome for the health system, and that, as in other cases, they do not use it excessively or inappropriately (22,27) .…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations
“…At the same time, nurses themselves think they should continue making an effort for immigrants to have a better quality of life. But these ideas are in contrast with the perception that immigrants receive more social assistance than Spaniards and that too many resources are devoted to the care of this social group, with immigrant patients being considered responsible for the collapse of our health system, which could in a not too distant future lead to serious health and social problems, coinciding with ideas obtained by different studies (1,17,(22)(23)(24)(25)(26) . Although this is the perception of nurses, it has been demonstrated that immigrants do not use hospital services more frequently than the native population nor is this use more burdensome for the health system, and that, as in other cases, they do not use it excessively or inappropriately (22,27) .…”
Section: Discussioncontrasting
confidence: 42%
“…But if the questionnaire is analysed according to the dimensions proposed by Plaza-del Pino (1) , we find the following results: when analysing each item in relation to the gender variable, we found a significant difference on item 20 "To a large extent, the collapse of the public health system has been caused by the rise in immigration", pertaining to the dimension of Immigration and social rights, with women having a worse score than men (χ2=.001, M Woman =1.59, M Man =3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies addressing cultural disparity by nationality in Spain have indicated that Moroccans are the foreigners with the greatest cultural distance to Spaniards, primarily due to their Muslim religion [6,7]. There is rejection of the intense religiosity attributed to them by the host community, since it is considered to influence their daily life too much and to hinder their integration into Spanish society.…”
Section: Introductionmentioning
confidence: 99%